Bioaccumulation and ecotoxicity of parabens in aquatic organisms: Current status and trends - da Silveira, Felipe Félix Costa Lima; Porto, Viviane Amaral; de Sousa, Bianca Leite Carnib; de Souza, Emilly Valentim; Lo Nostro, Fabiana Laura; Rocha, Thiago Lopes; de Jesus, Lázaro Wender Oliveira [UNESP] (Elsevier, 2024)
Parabens are preservatives widely used in personal care products, pharmaceuticals, and foodstuffs. However, they are still unregulated chemical compounds. Given their extensive use and presence in different environmental compartments, parabens can adversely affect animal health. Thus, the current study aimed to summarize and critically analyze the bioaccumulation and ecotoxicity of parabens in aquatic species. Studies have been mostly conducted in laboratory conditions (75%), using mainly fish and crustaceans. Field studies were carried out across 128 sampling sites in six countries. Paraben bioaccumulation was predominantly detected in fish muscle, liver, brain, gills, ovary, and testes. Among the parent parabens, methylparaben (MeP), ethylparaben (EtP), and propylparaben (PrP) have been detected frequently and more abundantly in tissues of marine and freshwater specimens, as well as the metabolite 4-hydroxybenzoic acid (4-HB). Parabens can induce lethal and sublethal effects on aquatic organisms, such as oxidative stress, endocrine disruption, neurotoxicity, behavioral changes, reproductive impairment, and developmental abnormalities. The toxicity of parabens varied according to species, taxonomic group, developmental stage, exposure time, and concentrations tested. This study highlights the potential bioaccumulation and ecotoxicological impacts of parabens and their metabolites on aquatic invertebrates and vertebrates. Additionally, future research recommendations are provided to evaluate the environmental risks posed by paraben contamination more effectively.
Keywords: Aquatic pollution; Ecotoxicology; Endocrine disruption; Esters of p-hydroxybenzoic acid; Sentinel species; Zebrafish